Results of propagation of Fagus silvatica L. plants in vitro - Mykola Lisovyi; Andrii Ivaniuk (Наукові праці Лісівничої академії наук України)
A number of experimental studies have been conducted regarding the modification of the main stages of microcloning of Fagus silvatica L., namely: features of decontamination of plant material, initiation of growth and rhizogenesis of explants and adaptation of clones to in vivo conditions. The influence of the concentration and duration of treatment with chemical sterilant agents on the yield of aseptic explants of the species under study is characterized. The methodology for conducting experimental studies on the reproduction of Fagus silvatica L. in vitro culture is presented. It was found that it is most effective to use apical buds, harvested in the second half of February, as the starting plant material.